Punch needle embroidery as an art therapy to overcome mild depression / Nurul Farah Shazleen Sarajuddin and Rose Dahlina Rusli - Sarajuddin, Nurul Farah Shazleen; Rusli, Rose Dahlina (Universiti Teknologi MARA, Perak, 2020)
Punch needle is another tool of embroidery that uses a hollow needle to create loops of thread on fabric. It is also known as thread painting for the texture and complexity of the design and this technique. This art and tool are easy to handle and can create cool stuff with it. This punch needle has a variety of sizes for the needle, same goes as the thread so it can fit in and just punch through the cloth. With this exploration and experiment of sampling, such as the pattern, shape, colour and then the researcher can finalise the good quality for the respondent and also search some motivational words to build up confidence for mild depression. The objectives are to establish the punch needle embroidery as a one of art therapy methods in conveying mild depression and to develop interest in punch needle embroidery amongst youngsters through pattern design. The target of this research is to focus on youngsters having mild depression. Punch needle embroidery is another method of art therapy for them to overcome the illness. The researcher will be collecting by interviewing some psychologists, psychiatrists and doing some online survey through google form and collect 100 respondents according to this issue. The respondents give some idea for the pattern or some motivational words that can make them feel stronger and can brighten up their day.